THE IMPLEMENTATION OF THE AMTSILATI METHOD TO IMPROVE READING SKILLS OF CLASSICAL ISLAMIC TEXTS IN INDONESIAN PESANTREN - Saipul Wakit; Margiyono Suyitno; Alfi Fuadah; Rif’ah; Abdul Kholid Achmad (Referensi Islamika: Jurnal Studi Islam, 2026)
For learning in Islamic boarding schools to be effective and efficient, it must be supported by appropriate methods. With the advancement of science and technology, simple and concise methods for understanding the science of nahwu sharaf (study of Islamic texts) as the basis for reading classical Islamic textss (kitab kuning) have emerged. This study describes how the Amtsilati method is implemented and how teachers and students perceive its contribution to learning. This study used a qualitative case study approach conducted in an Islamic boarding school. Data were collected through observation, interviews, and documentation, and analyzed using dialogical interpretation of theory and empirical findings to reach credible conclusions. The results indicate that the implementation of the Amtsilati method consists of three stages: planning carried out by the teacher before the lesson begins by outlining learning indicators. Implementation involves collaborative and student-centered learning through repeated reading, memorizing qaidah (religious rules), reciting nadham (proverbs), and analyzing examples based on nahwu and sharaf (study of Islamic texts). Evaluation is carried out through two forms: written and oral competency tests. The Amtsilati method makes it easier to understand Arabic grammar, with an effective and efficient learning design using a collaborative central learning model based on memorizing poetry and rules. This research focuses on the implementation of the Amtsilati learning method, which includes planning, implementation, and evaluation of learning. Further research will focus on the level of learning effectiveness on students' understanding of Amtsilati lessons using quantitative research.